Pengetahuan Lokal Masyarakat Desa Cihanjuang, Kabupaten Sumedang tentang Bencana Longsor: Pendekatan Antropologi dan Geologi - Fathimah Shidqi; Faishal Muhammad Shiddiq; Benedictus Beryl Franklyn Maspaitella; Hilfi Taufiqul Rahman; Moh. Fahrul Yahya (Umbara, 2021)
This research aims at describing local knowledge about landslides among residents living in a landslide prone area; using Anthropological and Geological approach. In January 2021, a landslide occurred and killed 40 victims. This research uses qualitative and quantitative methods. Data were collected based on the Anthropology and Geology approach. Primary data were obtained through participatory observation, in-depth interviews, survey, and mapping using GIS technology. The results of this research indicate that geologically, the research location is prone to landslides. The residents have a lack of knowledge and experience about disasters, in particular landslides. Furthermore, they lack knowledge about the geological facts of the housing area. They trust the government and the developer who built the housing which they believe had considered the security of their housing.